Perancangan dan Pembuatan Website Puskesmas Kaliwates Jember sebagai Media Informasi Pelayanan Kesehatan dan Promosi Kesehatan - Resti Aprilia Tri Hendaryanti; Feby Erawantini; Sustin Farlinda; Niyalatul Muna (Politeknik Negeri Jember, 2021)
Kaliwates Jember Health Center is one of the health centers that does not have a website as a medium of information and promotion to the public, so that the public lacks information related to the health center. The purpose of this research was to design and to create a website of Kaliwates Jember Health Center. Researchers used qualitative research and used the waterfall model system design method. The stages in this method included Requirement Analysis and Definition,System and Software Design, Implementation and testing, Integration and system testing and Operation and maintenance. In the process of designing this system the researchers used a Flowchart system, Contex Diagram, Data Flow Diagram, Entity Relationship Diagram and in implementing programs they used notepad ++ and xampp. The strengths of the website that have been made are the doctor's questioning service for patients to be able to communicate with doctors in the Kaliwates Puskesmas without having to come to the puskesmas, patients can register online for treatment, there are statistical data about the number of patient visits through the website.It is expected that the development of existing websites such as distinguishing questions asked by doctors coming from new patients and old patients and hopefully, the future researchers will get more complete data related to puskesmas.